RET Inhibitor SPP86 is a Potential Candidate for the Clinical Treatment of Cutaneous Melanoma [Response to Letter] - Zhang Y; Liu H; Wang K; Zheng J; Luan H; Xin M (Drug Design, Development and Therapy)
Yuli Zhang,1,2 Haidong Liu,1 Kun Wang,3 Juan Zheng,4 Hong Luan,1 Ming Xin5 1Department of Dermatology, Liaocheng People’s Hospital, Liaocheng, Shandong, People’s Republic of China; 2Department of Endocrinology, The Second Hospital of Shandong University, Jinan, Shandong, People’s Republic of China; 3Department of Endocrinology and Metabology, Liaocheng, People’s Hospital, Liaocheng, Liaocheng, Shandong, People’s Republic of China; 4Joint Laboratory for Translational Medicine Research, Liaocheng People’s Hospital, Liaocheng, Shandong, People’s Republic of China; 5The Key Laboratory of Molecular Pharmacology, Liaocheng People’s Hospital, Liaocheng, Shandong, People’s Republic of ChinaCorrespondence: Ming Xin, The Key Laboratory of Molecular Pharmacology, Liaocheng People’s Hospital, Liaocheng, Shandong, People’s Republic of China, Email xinming137@163.com Hong Luan, Department of Dermatology, Liaocheng People’s Hospital, Liaocheng, Shandong, People’s Republic of China, Email lcsrmyy@126.com